2011
DOI: 10.1111/j.1600-0528.2010.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of health promotion and fluoride varnish on dental caries among Australian Aboriginal children: results from a community-randomized controlled trial

Abstract: ObjectivesWe tested a dental health program in remote Aboriginal communities of Australia's Northern Territory, hypothesizing that it would reduce dental caries in preschool children.MethodsIn this 2-year, prospective, cluster-randomized, concurrent controlled, open trial of the dental health program compared to no such program, 30 communities were allocated at random to intervention and control groups. All residents aged 18–47 months were invited to participate. Twice per year for 2 years in the 15 interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(208 citation statements)
references
References 15 publications
8
194
2
Order By: Relevance
“…Because of these variations in reporting, the caries-free proportion was calculated from papers that reported caries prevalence (percentage with caries). Data were entered into a 20 Cross-sectional dmft/DMFT Not reported Endean et al (2004) 21 Cross-sectional dmft/DMFT Not reported Armfield (2005) 22 Cross-sectional dmft/DMFT Not reported Blair et al (2005) 23 Cross-sectional dmft/DMFT Not reported Kruger et al (2005) 24 Cross 27 Cross-sectional dmft/DMFT WHO 1997 28 Cross-sectional dmft/DMFT Not reported Hopcraft and Chow (2007) 29 Cross-sectional dmft/DMFT Visually apparent cavitation, discolouration showing through enamel or visual evidence of recurrent caries SiC SiC10 30 Cross-sectional dmft/DMFT Not reported SiC SiC10 Bailie et al (2009) 31 Cross-sectional dmft/DMFT Not reported Spencer et al (2010) 32 Cross-sectional dmft/DMFT Not reported Jamieson et al (2010) 33 Longitudinal cohort dmft/DMFT Untreated decay diagnosed as cavitation of enamel or dentinal involvement or both being present Dogar (2011) 3 Cross-sectional dmft/DMFT WHO 1997 Slade et al (2011) 34 RCT dmfs Cavitation-visible break in the enamel surface Divaris et al (2013) 35 RCT dmfs Cavitation-visible break in the enamel surface Zander et al (2013) 36 Cross-sectional dmft/DMFT Caries diagnosis taken from enamel cavitation Ha, ACPOHR (2014) 37 Cross-sectional dmft/DMFT WHO 1997 Johnson et al (2014) 38 Cross-sectional dmft/DMFT WHO 1997 Lalloo et al (2014) 39 Cross-sectional dmft/DMFT Clinical judgement Microsoft Excel (Redmond, WA, USA) spreadsheet and examined for any duplication of data in studies by the same authors. Rural and urban location was extracted from papers where this was reported.…”
Section: Data Extractionmentioning
confidence: 99%
“…Because of these variations in reporting, the caries-free proportion was calculated from papers that reported caries prevalence (percentage with caries). Data were entered into a 20 Cross-sectional dmft/DMFT Not reported Endean et al (2004) 21 Cross-sectional dmft/DMFT Not reported Armfield (2005) 22 Cross-sectional dmft/DMFT Not reported Blair et al (2005) 23 Cross-sectional dmft/DMFT Not reported Kruger et al (2005) 24 Cross 27 Cross-sectional dmft/DMFT WHO 1997 28 Cross-sectional dmft/DMFT Not reported Hopcraft and Chow (2007) 29 Cross-sectional dmft/DMFT Visually apparent cavitation, discolouration showing through enamel or visual evidence of recurrent caries SiC SiC10 30 Cross-sectional dmft/DMFT Not reported SiC SiC10 Bailie et al (2009) 31 Cross-sectional dmft/DMFT Not reported Spencer et al (2010) 32 Cross-sectional dmft/DMFT Not reported Jamieson et al (2010) 33 Longitudinal cohort dmft/DMFT Untreated decay diagnosed as cavitation of enamel or dentinal involvement or both being present Dogar (2011) 3 Cross-sectional dmft/DMFT WHO 1997 Slade et al (2011) 34 RCT dmfs Cavitation-visible break in the enamel surface Divaris et al (2013) 35 RCT dmfs Cavitation-visible break in the enamel surface Zander et al (2013) 36 Cross-sectional dmft/DMFT Caries diagnosis taken from enamel cavitation Ha, ACPOHR (2014) 37 Cross-sectional dmft/DMFT WHO 1997 Johnson et al (2014) 38 Cross-sectional dmft/DMFT WHO 1997 Lalloo et al (2014) 39 Cross-sectional dmft/DMFT Clinical judgement Microsoft Excel (Redmond, WA, USA) spreadsheet and examined for any duplication of data in studies by the same authors. Rural and urban location was extracted from papers where this was reported.…”
Section: Data Extractionmentioning
confidence: 99%
“…Community-based health promotion and disease prevention approaches, such as the promotora model, hold potential to address this need, with a growing body of literature documenting promising efficacy for promoting child nutrition and preventing common childhood illnesses, inclusive of dental caries [24, 43,44]. In their role as both health promoter and community member, they possess unique contextual and cultural knowledge that can prove invaluable for ensuring prevention efforts penetrate into medically-underserved regions, particularly in the context of obesogenic and cariogenic environments (e.g., rapid access to stores selling junk food).…”
Section: Implications For Addressing Oral Health and Malnutrition In mentioning
confidence: 99%
“…Fluoride varnishes have gained popularity due to their high concentration and safety during application (8). A number of studies have demonstrated that fluoride varnishes are able to remineralize incipient carious lesions as well as prevent decay when used with other preventive measures, such as diet control and reduction of dental biofilm (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%